Parents Attention to Students' Learning Achievements (Study on Students with Low Achievements in Class XI SMA N 1 Siberut Utara) - AURELIA, SITI (Holistic Science, 2022)
This research is motivated by the lack of parental attention in student learning, there are still parents of students who are not present at the meeting of parents and teachers because of busy work and there are still students who are less confident in their learning abilities. The purpose of this study is to describe the attention of parents in terms of: 1) Supervising the learning process of students. 2) Motivating student learning. 3) Meet the learning needs of students. 4) Guiding students in learning. This research was conducted using a quantitative descriptive method with the research population of 31 students and the total sample of students selected by total sampling technique. The instrument used is a questionnaire. The data were analyzed using the percentage formula. The results of the study were concluded as follows: 1) Supervising the learning process of students had a fairly good percentage of 51.61% and 3.23% good. 2) Motivating students' learning has a fairly good percentage of 80.65% and 19.35 is not good. 3) Meeting the learning needs of students has a fairly good percentage of 67.74% and 6.45% good. 4) Guiding students in learning has a very poor percentage of 71.00% and 29.03% less good. Based on the results of this study, it is recommended that parents can be more controlling and ask students about students' learning constraints and it is recommended for students to increase their internal motivation so that their learning achievement increases